2015
DOI: 10.1177/1479164115579005
|View full text |Cite
|
Sign up to set email alerts
|

Survival of diabetes patients with major amputation is comparable to malignant disease

Abstract: Introduction: Almost all studies on diabetic foot syndrome focused on prevention of amputation and did not investigate long-term prognosis and survival of patients as a primary outcome parameter. Methods:We did a retrospective cohort study including 314 patients who had diabetic foot syndrome and underwent amputation between December 1995 and January 2001. Results: A total of 48% of patients received minor amputation (group I), 15% only major amputation (group II) and 36% initially underwent a minor amputation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
0
27
0
4
Order By: Relevance
“…Despite having lower incidence rates of major LEAs several studies, including ours, suggest that women have higher mortality rates associated with diabetes-related LEAs [36, 37]. In US have reported that women had higher IHM associated with diabetes-related LEAS (37.7 IHM/1000 amputations vs. 29.7/1000 amputations [38].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Despite having lower incidence rates of major LEAs several studies, including ours, suggest that women have higher mortality rates associated with diabetes-related LEAs [36, 37]. In US have reported that women had higher IHM associated with diabetes-related LEAS (37.7 IHM/1000 amputations vs. 29.7/1000 amputations [38].…”
Section: Discussionmentioning
confidence: 82%
“…Patients who needed major amputations suffered from a more severe cardiovascular disease than others [36]. Previous studies in Spain, significant risk factors for IHM were cardiac and respiratory complications and first episode of amputation [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Между тем немногочисленные ис-следования данного показателя, отмечают, что прогноз выживания пациентов с СДС, особенно после ампута-ций нижних конечностей значительно хуже, чем у онко-логических больных [2]. Следует отметить, что прогноз жизни зависит от уровня ампутаций; так, средний срок выживания в группе пациентов с СД с малыми ампута-циями составил 51 мес, что оказалось достоверно боль-ше, чем в группе пациентов с высокими ампутациями, -40 мес (p=0,016) [3]. При этом по стоимости лечения СДС представляет одну из наиболее затратных патологий.…”
Section: обоснованиеunclassified
“…Despite new therapeutic advances, many patients still develop various forms of DFS at different stages. DFS is associated with a high rate of amputation and excessive mortality . It was estimated that every minute, two lower limbs or parts of a lower limb are lost somewhere in the world as a consequence of DFS .…”
Section: Introductionmentioning
confidence: 99%